Digital and Social Media Marketing as a Core Strategy in Higher Education: Evidence from Student Engagement and Institutional Branding - Muchlis Abbas (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to examine the role of digital and social media marketing as a core strategic mechanism in higher education, with particular emphasis on its influence on student engagement and institutional branding. The research adopts a qualitative systematic literature review approach by synthesizing evidence from 127 empirical studies published between 2015 and 2025 that investigate relationships among social media marketing activities, student engagement, and branding outcomes in higher education institutions. The review integrates findings from diverse methodological traditions and institutional contexts to identify recurring patterns, explanatory mechanisms, and strategic implications. The results reveal that digital and social media marketing exerts strong and consistent direct effects on student engagement and institutional branding, while also operating indirectly through engagement-driven pathways that partially mediate branding outcomes. Student engagement is found to play a central role in translating digital marketing activities into brand equity components, including brand awareness, brand image, perceived quality, and brand loyalty. The findings further indicate that content quality, authenticity, and platform-specific strategies function as critical determinants of marketing effectiveness. Overall, the study concludes that social media marketing constitutes a foundational institutional strategy rather than a peripheral communication tool, and its strategic integration is essential for sustainable branding and competitiveness in contemporary higher education environments.